ARTIFICIAL INTELLIGENCE ON TEACHING AND LEARNING OF SCIENCE EDUCATION PROGRAMME IN TERTIARY INSTITUTIONS IN NORTH-CENTRAL, NIGERIA - Okwelogu Izunna Somadina; Olamoyegun Stephania Olabisi (International Journal of Artificial Intelligence for Digital Marketing, 2024)
The study assessed the effects of artificial intelligence on teaching and learning of science education programme in tertiary institutions in Nigeria. The study used descriptive survey method. The population of the study comprises of all academic staff in North-Central Nigeria. The sample for the study was made up of 200 academic staff in the region. The researcher formulated an instrument titled Artificial Intelligence and Science Education Questionnaire (AISEQ). Test and re-test method was used to determine the reliability of the instrument. The result collected on the first and second were correlated and it yielded a coefficient of 0.86 which is high enough for the study. Descriptive statistics was used to analyze data collected for the research questions and hypothesis formulated for the study. The result collected and analyzed disclosed that Al support implementation of science education in Nigerian Tertiary institution in the following areas; Al supports presentation of lecture on science education, assists lecturers to carry out researches in science education, helps lecturer to provide community services, assists lecturers to develop course note, aids effective classroom management, assists lecturers to assign assignments and projects to students, support distance learning education, support individual learning and collaborate learning, assists students in writing research work, assists effective examinations in tertiary institutions and support practical work in laboratory. The result established that artificial intelligence has aided teaching and learning of science education in Nigerian tertiary institutions. Based on this, the study recommended that the tertiary institutions manager should increase funding of science education to enable the procurement and deployment of Al for the teaching and learning of science education in Nigerian tertiary institutions.